BIOSORPSI ION LOGAM Cr(VI) DENGAN MENGGUNAKAN BIOMASSA LAMUN Enhalus acoroides YANG TERDAPAT DI PULAU BARRANG LOMPO - Nursiah La Nafie; Paulina Taba; Djasmawati Mahmud (Hasanuddin University, 2009)
Biosorption is an alternative technique which can be used in solving environmental pollution coming from waste containing heavy metals. Biosorption of Cr(VI) ion using biomass of seagrass, Thalassia hemprichii at various contact time, pH and concentration has been investigated. Biosorption was performed by a batch method and concentration of ions before and after biosorption were measured by atomic absorption spectrophotometer (AAS). The equilibrium was achieved after 80 minutes. Adsorption effectivity of Cr(VI) Enhalus acoroides ion was pH 2. Biosorption of Cr(VI) ion by using biomass of Enhalus acoroides followed Langmuir isotherm and the result showed that biosorption capacity (Qo) of Cr(VI) ion was 8.13 mg/g.Keywords: biosorption, Cr(VI), seagrass, Enhalus acoroides, Langmuir isotherm.